Plasma lipoxin A4 levels in childhood chronic spontaneous urticaria - Dilek, Fatih; Özçeker, Deniz; Güler, Eray Metin; Özkaya, Emin; Yazıcı, Mebrure; Tamay, Zeynep; Koçyiğit, Abdurrahim; Güler, Nermin (The Turkish Journal of Pediatrics, 2018)
Chronic spontaneous urticaria (CSU) is an idiopathic inflammatory disorder. Despite great research progress, the pathogenesis of the disease is still not fully understood. Lipoxins (LXs) are autacoid lipid metabolites that are the first discovered members of a new genus named called `specialized proresolving mediators`. In this study, we aimed to investigate the possible role of LXA4 in the pathogenesis of CSU. Forty-two children with CSU and 25 healthy children were enrolled in the study. The demographic and clinical features of patients were evaluated, autologous serum skin tests (ASSTs), and routine laboratory assessments were performed. Disease activity was determined using the urticaria activity score. An enzyme-linked immunosorbent assay was used to evaluate LXA4 plasma levels. The median value of plasma LXA4 was found to be 60.8 ng/ml (interquartile range, 48.1-71.8) in CSU patients and 137.4 ng/ml (121.4-150.8) in the control group. The difference between the groups was statistically significant (p < 0.001). Additionally, the median plasma LXA4 levels in the ASST-positive patients were significantly reduced compared to the ASST-negative ones (45.8 [36.7-67.6] versus 63.8 [58.3-78.9] ng/ml, respectively, p < 0.05). Our results showed that diminished LXA4 biosynthesis may be a critical part of CSU pathogenesis in children, especially in patients with an autoimmune component.
Keywords: children; chronic spontaneous urticaria; disease severity; lipoxin A4